Effect of Rehydration on Recovery, Repair, and Growth of Injured Freeze-Dried Salmonella anatum - Ray, B. (1971)
From 70 to 90% of the Salmonella anatum cells that survived freeze-drying in nonfat milk solids were injured. After rehydration, these injured survivors failed to grow on a selective plating medium containing deoxycholate but could form colonies on a nonselective medium. In a suitable environment after rehydration, injury disappeared in most of these cells. The rate of this repair at 25 C was very rapid initially and, in a medium containing milk solids, was completed within 1 hr after rehydration. The repaired cells initiated growth about 1 hr later than normal cells and grew at a slower rate. In a medium containing milk solids, initial recovery, extent of repair of injury, initiation of growth, and rate of growth were not influenced by supplementation with extra nutrients in other rehydration media. Rehydration controlled by modifying the concentrations of lactose, sucrose, or milk solids in the rehydration medium influenced the recovery of cells and the time that growth was initiated. Glycerol failed to increase recovery. Higher numbers of cells were recovered by rehydrating at 15 to 25 C, but an earlier initiation of growth and more rapid growth were observed at 35 C.